2017
DOI: 10.1016/j.meatsci.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

On-farm conditions that compromise animal welfare that can be monitored at the slaughter plant

Abstract: Handling and stunning at slaughter plants has greatly improved through the use of numerical scoring. The purpose of this paper is to encourage the use of numerical scoring systems at the slaughter plants to assess conditions that compromise welfare that occurred either during transport or on the farm. Some of the transport problems that can be assessed are bruises, death losses, and injured animals. Welfare issues that occurred on the farm that can be assessed at the abattoir are body condition, lameness, lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 79 publications
0
53
0
10
Order By: Relevance
“…Body condition is widely accepted as a valid and important welfare measure that reflects the nutritional state of sheep [13,14]. Results in the present study suggests that a quarter-point scale is reliable, but that operators require sufficient training and experience to achieve high agreement in this measurement [27,35,36]. In this study, the experienced observers (TSO, observers 2 and 7) showed the highest agreement and repeatability for this measure.…”
Section: Discussionmentioning
confidence: 57%
“…Body condition is widely accepted as a valid and important welfare measure that reflects the nutritional state of sheep [13,14]. Results in the present study suggests that a quarter-point scale is reliable, but that operators require sufficient training and experience to achieve high agreement in this measurement [27,35,36]. In this study, the experienced observers (TSO, observers 2 and 7) showed the highest agreement and repeatability for this measure.…”
Section: Discussionmentioning
confidence: 57%
“…Apple (1999) mentioned that BCS can be useful to both cow-calf producers and slaughter-cow processors in making market decisions. Measuring BCS can be considered highly feasible, however, some scores have too many categories and suffer from inter-observer variability (Grandin, 2017). Halachmi, Klopcic, Polak, Roberts, & Bewley (2013) report that results depend on the person scoring, familiarity with the cows, and consistency between scoring periods, suggesting the use of a device for automatic (objective) monitoring of body condition, such as thermographic cameras or ultrasound scanning.…”
Section: Morphometric Indicatorsmentioning
confidence: 99%
“…Loading and unloading conditions will influence the quality of lairage time; however, lairage under poor conditions will also affect animal behaviour. Grandin (2017) mentions the wide variation among cattle behaviour during lairage, based on reports by abattoir personnel; cattle can be difficult or easy to move and the former are more likely to be abused. That may be explained by differences in emotional reactivity, i.e., the tendency to show pronounced reactions to different fear-inducing situations (Bourguet et al, 2010).…”
Section: Behavioral Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations